Chapter 3 Mending "Moors" in Mogador Hajj, cholera and Spanish-Moroccan regeneration, 1890-99 - Javier Martinez, Francisco (Social Histories of Medicine, 2018)
This chapter deals with a rather unknown quarantine institution: the lazaretto of Mogador Island in Morocco. Specifically, the work explores the site's centrality to the Spanish imperialist project of "regeneration" over of its southern neighbour. In contrast with the "civilisation" schemes deployed by the leading European imperial powers at the end of the nineteenth century, regeneration did not seek to construct a colonial Morocco but a so-called African Spain in more balanced terms with peninsular Spain. This project was to be achieved through the support and direction of ongoing Moroccan initiatives of modernisation, as well as through the training of an elite of "Moors" who were to collaborate with Spanish experts sent to the country, largely based in Tangier. Within this general context, the Mogador Island lazaretto became a key site of regeneration projects. From a sanitary and political point of view, it was meant to define a Spanish-Moroccan space by marking its new borders and also to protect "Moorish" pilgrims against both the ideological and health-related risks associated with the Mecca pilgrimage.